PERAN SERTA MASYARAKAT DALAM PENGELOLAAN SUMBER DAYA IKAN DI KABUPATEN BENGKALIS DALAM PERSPEKTIF HUKUM LAUT NASIONAL - Adi TiaraPutri; Ledy Diana (Faculty of Law, Universitas Riau, 2018)
The State regulates the procedures for the management of fish resources that are contained in various regulations. The State also provides space for the community to manage fish resources. In the management of fish resources based on the principles of management. The management of fish resources includes also controlling of fish resources. Bengkalis Regency is the coastal areas which has potential fish resource, terubuk fish. The research method used the normative method with approach of legislation concerning the role of the community in the management of fish resources.Keywords : Fish Resources, Management, National Law